Effectiveness of a Novel Liposomal Methylglyoxal–Tobramycin Formulation in Reducing Biofilm Formation and Bacterial Adhesion - Wed Alluhaim; Manal M. Alkhulaifi; Raghad R. Alzahrani; Bahauddeen M. Alrfaei; Alaa Eldeen B. Yassin; Majed F. Alghoribi; Ahlam M. Alsaadi; Ahmed I. Al-Asmari; Ahmed J. Al-Fahad; Rizwan Ali; Naif M. Alhawiti; Majed A. Halwani (Antibiotics)
Background: The emergence of multidrug-resistant bacteria presents a significant global health threat. Liposomal antibiotics have shown a potential to improve antibiotic delivery and efficacy. This study aimed to develop liposomes encapsulating tobramycin (TOB) and methylglyoxal (MGO) to enhance TOB activity while reducing bacterial adhesion and biofilm formation. Methods: Clinical isolates of Pseudomonas aeruginosa and Klebsiella pneumoniae were characterized using whole-genome sequencing. Liposomes (Lip-MGO-TOB) were formulated using Manuka honey as a surfactant and loaded with MGO and TOB. Antibacterial activity, biofilm formation, and bacterial cell adhesion assays were performed to compare the efficacy of Lip-MGO-TOB against free TOB. Liposome characterization included analyses of morphology, zeta potential, TOB encapsulation efficiency, and stability under various biological conditions. Results: The Lip-MGO-TOB formulation, at a minimum inhibitory concentration (MIC) of 32 µg/mL, reduced the biofilm formation of the P. aeruginosa isolate (PA85) by 68%. Conversely, free TOB, at a MIC of 64 µg/mL, achieved only a 21% reduction. For the K. pneumoniae isolate (KP57), Lip-MGO-TOB inhibited bacterial adhesion to A549 cells at a lower concentration (256 µg/mL) compared to free TOB (512 µg/mL). Lip-MGO-TOB demonstrated sustained drug release over 24 h under tested conditions and retained over 99% of TOB. Conclusions: The Lip-MGO-TOB formulation significantly enhanced TOB activity against resistant bacteria compared to free TOB. Additionally, it provided a stable drug delivery system with controlled drug release. Liposomal TOB represents a promising advancement in combating antibiotic resistance by improving the efficacy and delivery of conventional antibiotics.